RESEARCH OF OPERATING MODES OF A PULSE HYDRAULIC DRIVE OF WORKING BODIES OF AGRICULTURAL MACHINERY - YALYNA, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Hydraulic systems are used in almost all branches of agricultural machinery. They are widely used in production - for example, in foundry machines, presses, heavy manipulators, machine tools, works, molding machines for plastics. They play an important role in the operation of equipment designed for the mining and oil industry, in rescue equipment. And, of course, one of the widest areas of application for hydraulics is various kinds of special equipment: excavators and cranes, loaders, aerial platforms, agricultural, warehouse and many other types of machines. The use of hydraulic systems is due to a number of obvious advantages. First of all, they provide the efficiency of moving heavy loads with fine adjustment. Hydraulic systems also have great flexibility to control large and small forces. Another important benefit is reliability: equipment can be protected from overloading with simple pressure relief valves. Compared to the tasks they solve, hydraulic systems are compact and economical. The hydraulic system of any special equipment is a rather complex and precise mechanism. The performance of the machine largely depends on its ideal operation. An analysis of the development of modern foreign mobile machines, including earth-moving, leveling, lifting and transport, for the production of concrete work and soil compaction, agricultural and forestry machines, basic wheeled tractors, etc., revealed a trend towards a growing volumetric hydraulic drive. reciprocating and rotary motion. The author examines the modes of operation of the pulse hydraulic drive of the working bodies of agricultural machines, determines what their advantages and disadvantages, what types and designs of pulse hydraulic drives and how they affect the work process.